Case Report: Occurrence of Severe Thoracic Aortic Aneurysms (Involving the Ascending, Arch, and Descending Segments) as a Result of Fibulin-4 Deficiency: A Rare Pathology With Successful Management - Thomas, Paul; Venugopalan, Aparna; Narayanan, Siddharth; Mathew, Thomas; Cherukuwada, Lakshmi Parvathi Deepti; Chandran, Shilpa; Pradeep, Jithu; Fitzgibbons, Timothy P.; George, Vijo (Frontiers in Cardiovascular Medicine, 2021)
Aortic diseases requiring surgery in childhood are distinctive and rare. Very few reports in the literature account for the occurrence of multiple thoracic aortic aneurysms in the same pediatric patient because of a genetic cause. We report a rare occurrence of severe thoracic aortic aneurysms (involving the ascending, arch and descending aortic segments) with severe aortic insufficiency in a 7-year-old female child secondary to the extremely rare and often lethal genetic disorder, cutis laxa. She was eventually identified as a carrier of a homozygous EFEMP2 (alias FBLN4) mutation. This gene encodes the extracellular matrix protein fibulin-4, and its mutation is associated with autosomal recessive cutis laxa type 1B that leads to severe aortopathy with aneurysm formation and vascular tortuosity. Parents of the child were not known to be consanguineous. Significant symptomatic improvement in the patient could be discerned after timely intervention with the valve-sparing aortic root replacement (David V procedure) and a concomitant aortic arch replacement. This is a unique report with a successful outcome that highlights the occurrence of a rare hereditary aortopathy associated with a high morbidity and mortality, and the importance of an early diagnosis and timely management. It also offers insight to physicians in having a very broad differential and multimodal approach in handling rare pediatric cardio-pathologies with a genetic predisposition.